2017
DOI: 10.5817/cp2017-1-6
|View full text |Cite
|
Sign up to set email alerts
|

Parental mediation, cyber victimization, adjustment difficulties, and adolescents with autism spectrum disorder

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 50 publications
1
15
0
2
Order By: Relevance
“…A lack of research makes it difficult to explain this finding. Wright [33] did not find support that high parental mediation moderated the relationship between cyberbullying victimization and anxiety among adolescents with autism spectrum disorder, although she found support for moderation in samples of typically developing adolescents [6,33]. Furthermore, much of the research linking peer rejection to anxiety among adolescents with ASD focuses on social anxiety [57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lack of research makes it difficult to explain this finding. Wright [33] did not find support that high parental mediation moderated the relationship between cyberbullying victimization and anxiety among adolescents with autism spectrum disorder, although she found support for moderation in samples of typically developing adolescents [6,33]. Furthermore, much of the research linking peer rejection to anxiety among adolescents with ASD focuses on social anxiety [57].…”
Section: Discussionmentioning
confidence: 99%
“…Other research has found that adolescents with disabilities were more likely to report distressing cyberbullying victimization when compared to adolescents without disabilities [18]. Wright [33] also found that cyberbullying victimization and face-to-face bullying victimization were associated among adolescents with ASD, and that cyberbullying victimization was also related to depression and anxiety among these adolescents. Taken together, these studies suggest that adolescents with special needs might be particularly vulnerable to cyberbullying victimization and the associated negative outcomes.…”
Section: Introductionmentioning
confidence: 98%
“…This point is even more important considering that children with special needs are more likely to become victims of cyberbullying than children without special needs [56,57,58]. In this context, [59] found that parental mediation had a buffering effect on the relationship between cyber victimization and depression in children with ASD. It may be favourable for parents to be aware of the content of their child’s media use as well as related problems in order to be able to consider it in the assessment of their child’s behaviour, and thus react to it in an adequate way.…”
Section: Discussionmentioning
confidence: 99%
“…They also suggested reduced opportunity for relationships, making friends and participation in leisure activities as possible causal factors, linked with increased loneliness. Wright (2017) in a survey of young autistic people (some with ID), found experience of cyber-victimization was associated positively with anxiety, depression and loneliness. It also supported parental mediation of technology-use as protective against the negative adjustment consequences associated with cyber-victimization.…”
Section: Risk Factors For Online Victimisation Of People With Idmentioning
confidence: 99%